2022
DOI: 10.3389/fcell.2022.1022422
|View full text |Cite
|
Sign up to set email alerts
|

Variable allelic expression of imprinted genes at the Peg13, Trappc9, Ago2 cluster in single neural cells

Abstract: Genomic imprinting is an epigenetic process through which genes are expressed in a parent-of-origin specific manner resulting in mono-allelic or strongly biased expression of one allele. For some genes, imprinted expression may be tissue-specific and reliant on CTCF-influenced enhancer-promoter interactions. The Peg13 imprinting cluster is associated with neurodevelopmental disorders and comprises canonical imprinted genes, which are conserved between mouse and human, as well as brain-specific imprinted genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Although paternal-specific contacts were observed along the entire imprinted domain, stronger signals were detected at Kcnk9 , centred around the CTCF-bound promoter and 3’ edge of the intron, and at a biallelic CTCF-bound region in the 5’ part of Trappc9 (Figure 4, Supplementary Figure 4). This second signal peaks in a Trappc9 intron previously identified as a putative regulatory region controlling tissue-specific expression of the domain ( Claxton et al, 2022 ). These paternal-specific contacts are mainly maintained in NPC, where the interaction with the Trappc9 intronic putative regulatory region is reinforced.…”
Section: Resultsmentioning
confidence: 94%
“…Although paternal-specific contacts were observed along the entire imprinted domain, stronger signals were detected at Kcnk9 , centred around the CTCF-bound promoter and 3’ edge of the intron, and at a biallelic CTCF-bound region in the 5’ part of Trappc9 (Figure 4, Supplementary Figure 4). This second signal peaks in a Trappc9 intron previously identified as a putative regulatory region controlling tissue-specific expression of the domain ( Claxton et al, 2022 ). These paternal-specific contacts are mainly maintained in NPC, where the interaction with the Trappc9 intronic putative regulatory region is reinforced.…”
Section: Resultsmentioning
confidence: 94%
“…How trappc9 loss-of-function causes the development of obesity is not clear. In mice, trappc9 is imprinted with a biased expression (∼70%) from the maternally inherited allele specifically in the brain and shows an equal expression from maternal and paternal alleles in peripheral tissues ( 41, 75 ). Mice with only the maternal allele of trappc9 mutated appear overweight, whereas mice with only the paternal allele mutated are normal ( 41 ), indicating that the development of obesity in trappc9 KO mice involves a loss of function mainly in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, trappc9 is imprinted in the brain with a maternal allele-biased expression (∼70%) and shows an equal biallelic expression in peripheral tissues ( 25, 59 ). Trappc9 mice with only the maternal allele mutated appear overweight, whereas mice with the paternal allele mutated are normal ( 25 ), indicating that obesity onset in trappc9 KO mice involves a loss of function mainly in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The latter view is supported by our finding of prominent Trappc9 expression in hypothalamic paraventricular and arcuate nuclei, which are major centres for the central regulation of energy homeostasis (Bruning & Fenselau, 2023). Furthermore, Trappc9 is genomically imprinted specifically in the murine brain with a preferential expression bias (∼70 %) from the maternally inherited allele (Claxton et al, 2022; Liang et al, 2020). Accordingly, it has been shown that the phenotypes of Trappc9 heterozygotes differ depending on the parental inheritance of the mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic imprinting is defined as parent-of-origin specific gene expression caused by epigenetic modifications that are inherited through either the maternal or paternal germline and maintained in somatic cells of the offspring (Ferguson-Smith, 2011;Tucci et al, 2019). Although genomic imprinting of Peg13 and Kcnk9 is conserved between mouse and human, this is not the case for the three neighbouring genes Trappc9, Chrac1 and Ago2 (Court et al, 2014), which are imprinted in murine brain tissue only where they show a ~70 % expression bias from the maternal allele (Claxton et al, 2022;Liang et al, 2020;Perez et al, 2015). To focus on the strongest phenotypes, we have limited our analysis in this study to homozygous mutant mice, while a recent report reported that heterozygotes with a maternally inherited mutation (m-/p+) display symptoms almost as severe as homozygote KOs, while paternal heterozygotes (m+/p-) resemble wildtype mice (Liang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%